Faktor yang Mempengaruhi Tingkat Fertilitas di Indonesia: Review Literatur - Ni Wayan Yustika Agustin Darki; Arief Wibowo (Universitas Airlangga, 2023)
Background: TFR in Indonesia in 2017 amounted to 2.4, meaning that the average child born to a woman during her childbearing age is 2-3 children. However, this figure has not met the RPJMN target in 2015, which is 2.1. The high fertility rate of a region has a negative impact such as population explosion, diminishing land, even causing food shortages, and increasing crime rates. Purpose: To identify factors related to fertility rates in Indonesia. Method: The method used was literature review by studying 11 points according to predetermined topics and themes. The databases used were Google Scholar, ScienceDirect, Pubmed, and DOAJ. Discussion: Factors that affect fertility were age, education, first marriage age, income, contraceptive use, maternal working status, etc. The higher the age of the mother was the greater the number of children born. Inversely proportional to age, the lower the age of first marriage was the higher the number of children born. While the higher the education was the smaller the number of children born. Conclusion: factors that affected fertility rate of age, education level, age of first marriage, income, number of family members, and use of contraceptives. This was inseparable from several other influencing factors such as norms and beliefs, socio-economic, environmental, and also demographic factors.